The Problem of the Compatibility of Civil Disobedience with Liberal Democracy in Contemporary Philosophy of Law - Černevičiūtė, Jūratė (Problemos, 2002)
The article considers topical issues in the current discussion on the problem of civil disobedience in the democratic state among the contemporary philosophers of law. This discussion includes, first, a short historical survey of the evolving forms of the civil disobedience from times of H. D. Toreau till current attempts to use the cyberspace for the acts of civil disobedience. Secondly, the analytical problem how to define the concept of “civil disobedience” is scrutinized, paying special attention to differences between the acts of civil disobedience and those of evasion and conscientious refusal. Thirdly, the idea that obedience to law is a moral duty is critically explored, accepting the conclusion of J. Feinberg that such obedience neither is prima facie duty nor can be deduced from other moral prima facie duties. In other respects, J. Rawls’ views on the conditions of the viability of the civil disobedience in the liberal democratic society are judged as most penetrating and acceptable.